Research on Effective Ways to Promote the Dissemination of Chinese Culture among Pakistani Students Studying in Chinese Universities - Wang, Yan (Pacific International Journal, 2026)
This study aims to systematically explore how to construct and implement an effective path for the dissemination of Chinese culture within Chinese universities, particularly targeting the specific group of Pakistani international students. Despite the increasingly close strategic cooperation between China and Pakistan, there are still some practical issues in deep humanistic exchanges, especially in the dissemination of culture to Pakistani students in China, such as one-way communication mode, insufficient adaptation of content to the audience, and lack of effect evaluation. This study adopts a problem-oriented methodology to construct research, aiming to bridge the gap between macro-level cultural initiatives and micro-level educational practices. By comprehensively utilizing literature analysis, cross-cultural communication theory, and educational practice observation, this study proposes a comprehensive path framework centered on "mutual adaptation" and "systemic embedding." This framework emphasizes that effective cultural dissemination must shift from isolated, symbolic activities to an interactive cultural practice ecosystem deeply embedded in the entire academic and life processes of universities. This study constructs a systematic path comprising four pillars: "academic curriculum cultural immersion," "integration into campus life experience," "digital platform interactive co-creation," and "peer network interpersonal support," and elaborates on the specific implementation strategies, potential challenges, and coordination mechanisms for each path. The conclusion of this paper is that only through this systematic, interactive, and sustainable methodological innovation can cultural dissemination be internalized into the positive cognition and emotional identification of Pakistani students, thereby truly serving the strategic goal of "humanistic connectivity" between China and Pakistan and laying a solid social and humanistic foundation for inter-generational friendship between the two countries.